2013
DOI: 10.1038/ismej.2013.187
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell genome and metatranscriptome sequencing reveal metabolic interactions of an alkane-degrading methanogenic community

Abstract: Microbial interactions have a key role in global geochemical cycles. Although we possess significant knowledge about the general biochemical processes occurring in microbial communities, we are often unable to decipher key functions of individual microorganisms within the environment in part owing to the inability to cultivate or study them in isolation. Here, we circumvent this shortcoming through the use of single-cell genome sequencing and a novel low-input metatranscriptomics protocol to reveal the intrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 46 publications
5
124
1
Order By: Relevance
“…Although there are many reports about the individual transcription shift in a mixed culture containing two microbes (30,31), the individual metabolism shift in a two-microbe coculture is not enough to represent the changes of the whole community. The recent development of metatranscriptome sequencing provides an attractive method to reveal the systems-level transcriptional response of the microbial community (32). Therefore, our future work will be focused on the investigation of the transcription and metabolic shift of each microbial community member with the extrinsic microbial perturbation and the interactions between the microbes by use of a metatranscriptomic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many reports about the individual transcription shift in a mixed culture containing two microbes (30,31), the individual metabolism shift in a two-microbe coculture is not enough to represent the changes of the whole community. The recent development of metatranscriptome sequencing provides an attractive method to reveal the systems-level transcriptional response of the microbial community (32). Therefore, our future work will be focused on the investigation of the transcription and metabolic shift of each microbial community member with the extrinsic microbial perturbation and the interactions between the microbes by use of a metatranscriptomic approach.…”
Section: Discussionmentioning
confidence: 99%
“…ME-1 (Embree et al, 2014;Tan et al, 2014A) (Figure 3). Five distinct putative assA genes were identified in SCADC (Figure 3), reflecting the diversity of alkane substrates degraded by this culture (Tan et al, 2013).…”
Section: Fumarate Addition Reactionsmentioning
confidence: 99%
“…Here we comment on three aspects of a recent report in ISME J (Embree et al, 2013), which concluded that: the draft genome of Smithella ME-1 lacks genes encoding alkylsuccinate synthase (ASS) subunits; it therefore does not express those genes when grown on n-hexadecane in mixed culture under methanogenic conditions; and it may use an alternate mechanism to initiate anaerobic n-hexadecane degradation. We have re-analyzed the draft genome of Smithella ME-1 and three metatranscriptomes, and reached conclusions opposite to those of Embree et al (2013).…”
mentioning
confidence: 99%
“…We have re-analyzed the draft genome of Smithella ME-1 and three metatranscriptomes, and reached conclusions opposite to those of Embree et al (2013).…”
mentioning
confidence: 99%